THE RELATIONSHIP OF BALANCE AND LEG MUSCLE STRENGTH WITH THE ABILITY OF STRAIGHT KICKS IN PENCAK SILAT ATHLETES FOSTERED BY DISPORA ACEH BESAR IN 2020 - Tuti Sarwita; Zulheri Is (Teunuleh Publisher, 2020)
Pencak silat is a sport that has long been competed in the national and international arena. The problems in this research are as follows: How is the relationship between balance and leg muscle strength with the ability of straight kicks to the big Aceh Dispora-assisted Pencak silat athletes. The purpose of this study was to determine how much the relationship between balance and leg muscle strength and the ability of straight kicks in the Pencak silat athletes assisted by the Aceh Besar Dispora. This study uses a quantitative approach with the type of correlation research method. The objective of this research is to determine whether there is a relationship between the two or three variables studied. As for the population in this study, all male athletes of the Pencak Silat Assisted by Dispora Aceh Besar, totaling 7 people. Based on the results of the research on the balance of the Pencak Silat athletes assisted by the Aceh Dispora with an average balance of 45 and a standard deviation of 9.4. While the results of leg muscle strength are 208 on average and the standard deviation of leg muscle strength is 46.84. From the calculation of the coefficient of determination of the balance contribution, the leg muscle strength was 2.161 in the very strong category. From the results of the percentage of research results Balance to the Ability of Straight Kicks 0.29%, while the results of leg muscle strength are 208 on average and the standard deviation of leg muscle strength is 46.84. From the calculation of the coefficient of determination of the balance contribution, the leg muscle strength is 2.161 in the very strong category. From the results of the percentage of research results Balance to the Ability of Straight Kicks 0.29%.